2022
DOI: 10.1021/acsaem.2c00984
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Reaction Kinetics of N–MnO2 Nanosheets with Oxygen Vacancies via Mild NH3·H2O Bath Treatment for Advanced Aqueous Supercapacitors

Abstract: Suffering from the sluggish kinetics resulting from the inferior conductivity of manganese dioxide (MnO 2 ), many endeavors have been devoted to promoting the electrochemical performance of MnO 2 . Doping heteroatoms into host materials has emerged as an effective strategy to generate lattice vacancies for fast diffusion of ions/electrons in MnO 2 -based materials for supercapacitors (SCs). To eliminate the use of dangerous solvents and the severe reaction conditions used in previous reports, in this work, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…71 The oxygen vacancies have been reported to be advantageous for electrochemical studies by offering more active sites. 72…”
Section: Mott−schottky Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…71 The oxygen vacancies have been reported to be advantageous for electrochemical studies by offering more active sites. 72…”
Section: Mott−schottky Studiesmentioning
confidence: 99%
“…The increase in carrier charge density by Na + preintercalation into MnO 2 lattice also suggests the formation of oxygen vacancies . The oxygen vacancies have been reported to be advantageous for electrochemical studies by offering more active sites …”
Section: Mott–schottky Studiesmentioning
confidence: 99%
“…They demonstrated that the CNT/graphene/N-doped -Co3S4 supercapacitor has energy and power densities of 37.69 Wh/kg and 8000 W/kg, respectively. In another study, the supercapacitor based on the CNT/graphene/N-doped-MnO 2 electrode exhibited energy and power densities of 75.3 Wh/kg and 18,100 W/kg, respectively [88]. Hybrid nanostructures have been used to design flexible supercapacitors.…”
Section: Cnt/graphene-based Supercapacitorsmentioning
confidence: 99%
“…15–17 Transition metal oxide (TMO) nanomaterials such as RuO 2 , V 2 O 5 , Fe 3 O 4 , MnO 2 , Co 3 O 4 , CuO, MoO 3 , and IrO 2 are used as electrode materials for supercapacitors. 18–28…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Transition metal oxide (TMO) nanomaterials such as RuO 2 , V 2 O 5 , Fe 3 O 4 , MnO 2 , Co 3 O 4 , CuO, MoO 3 , and IrO 2 are used as electrode materials for supercapacitors. [18][19][20][21][22][23][24][25][26][27][28] As a promising transition metal oxide, molybdenum trioxide (MoO 3 ) exhibits the advantages of rich valence state, high thermal stability and chemical stability. 29 MoO 3 with layered structure has been considered to be an alternative potential electrode material for energy storage devices due to its outstanding theoretical specific capacitance (2700 F g À1 ) and high electrochemical activity for supercapacitors.…”
Section: Introductionmentioning
confidence: 99%